Dinamika Kekerasan dalam Rumah Tangga dan Dampaknya terhadap Kesehatan Mental Anak: Systematic Literature Review - St. Hardiyanti Arif; Saskia Zalzabila; Sitti Nazwa Muzdalifa Minggus; St. Khaerunnisa; Dian Novita Siswanti; Eka Sufartianinsih Jafar (CV. ITTC INDONESIA, 2026)
Domestic Violence (DV) is a complex social problem with far-reaching impacts, particularly on children as the most vulnerable group. Children may not only become direct victims but also witnesses to repeated violence within the family environment. This study aims to systematically examine the dynamics of domestic violence and its impact on children’s mental health through a Systematic Literature Review (SLR) approach. The literature search included relevant national and international studies, focusing on forms of domestic violence, contributing factors, and its psychological, social, and developmental consequences for children. The findings indicate that domestic violence has a significant impact on children’s mental health, including anxiety, depression, psychological trauma, behavioral disorders, and impairments in emotional, social, and academic development. Furthermore, economic stress, maladaptive parenting patterns, prolonged household conflict, and unequal power relations within the family were identified as factors that reinforce the persistence of domestic violence. These findings highlight that domestic violence has the potential to perpetuate intergenerational cycles of violence if not addressed comprehensively. Therefore, multidisciplinary interventions involving families, schools, communities, and the state are essential to protect children and support the psychological recovery of child victims of domestic violence.